2017
DOI: 10.1177/0734904117740855
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on fire behaviors of flexible photovoltaic panels using a cone calorimeter

Abstract: Photovoltaic arrays are mounted on the surfaces of modern buildings to harness renewable energy. When a building catches fire, burning photovoltaic panels could worsen an already very hazardous environment. This work deals with the effect of building flame radiation on the fire behaviors of flexible photovoltaic panel installed in building-integrated photovoltaic systems. Cone calorimeter tests were conducted in air with a piloted ignition. The influence of heat flux on photovoltaic fire properties was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The causes of PV fires have been investigated by Wohlgemuth et al, who found that hot spots, high series resistance, and arcing were three typical ways that a PV module can be overheated to start a fire. The reaction‐to‐fire properties of two widely used building‐integrated photovoltaic (BIPV) panels were characterized over a wide range of incident heat fluxes in previous studies . PV fire safety issues are also emphasized in some standards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of PV fires have been investigated by Wohlgemuth et al, who found that hot spots, high series resistance, and arcing were three typical ways that a PV module can be overheated to start a fire. The reaction‐to‐fire properties of two widely used building‐integrated photovoltaic (BIPV) panels were characterized over a wide range of incident heat fluxes in previous studies . PV fire safety issues are also emphasized in some standards.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction-to-fire properties of two widely used building-integrated photovoltaic (BIPV) panels were characterized over a wide range of incident heat fluxes in previous studies. [11][12][13] PV fire safety issues are also emphasized in some standards. Both IEC 61730-2 14 and UL 1703 15 present sets of methods to address fire hazards of PV modules, including thermal cycling, hot spot endurance, and temperature tests.…”
Section: Introductionmentioning
confidence: 99%
“…Burning behavior was significantly affected by the structure of the surface layer and the honeycomb core, as discussed in [33]. Thermal and flammability properties of the tested material, including thermal inertia kρc and ignition temperature T ig , were deduced from cone calorimeter measurements according to ISO 5660 and calculations based on the correlation of ignition data, as described in [34][35][36][37]. These properties, estimated using the analytical procedure presented in [38,39], are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Although specific safety rules and regulations exist for installing and maintaining PV systems, continuous research is still required to improve knowledge about risk factors and mitigation measures [6]. In recent years, various studies have focused on the investigation and analysis of this phenomenon associated with photovoltaic systems, such as the case of Ju et al [7], who studied the fire properties of a flexible photovoltaic module (PVM) and found that polyethylene terephthalate is the main component responsible for the decomposition and burning of the flexible PVM. Vaverkova et al [8] analyzed the impact of photovoltaic power plants on vegetation and the associated fire hazards; as a result, they revealed that eliminating fire hazards is necessary to employ suitable vegetation management methods.…”
Section: Introductionmentioning
confidence: 99%